2023
DOI: 10.1002/slct.202301762
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cyanide‐free and Scalable Route for the ADAMTS‐5 Inhibitor GLPG1972: Synthesis of an Advanced Key Chiral Intermediate

Charan Kumar G,
Anusooya S,
Gaikwad Rajendra
et al.

Abstract: In this study we report a mild, efficient, scalable, cyanide‐free and environmentally‐benign procedure for synthesizing 5,5‐disubstituted hydantoins starting from alkylnitriles and diethyl carbonate. Synthesis of 5,5‐disubstituted hydantoins is typically carried out under harsh conditions with transition metal catalysts that are not preferable from a sustainability perspective. This procedure illustrates an elegant cyanide‐free synthesis of cyclopropyl‐substituted 5,5‐hydantoins starting from alkylnitriles tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%